The Canon of Lekë Dukagjini, a monumental work of the spiritual culture on dhe Albanian people (History, name, codification) - Muhadri, Besim; Kamberi, Kamber (Technium Social Sciences Journal, 2023)
The Canon of Lekë Dukagjini, known among Albanians as the Canon of the Mountains, or the Canon of Lekë, etc., is among the monumental works of the spiritual, and customary cultural heritage of the Albanians. Preserved over the centuries as an unwritten document, but strictly implemented, it undoubtedly represents an interesting and very important aspect, which has aroused the interest of scholars, both foreign and Albanian. The Canon of Lekë Dukagjini, was compiled and codified in the first part of the twentieth century, by Shtjefën Gjeçovi, and it was published as a book in 1933. In my paper I address issues related to the name, but also the authorship of this important document, where scholars are divided into two parts: One part who think that the Canon belongs to Lekë Dukagjini, a prince of the XV century, while the other part go even further, thinking that it belongs to the time of Alexander the Great. The work in question is also considered as evidence of the culture of the European Renaissance and a unique work with a humanistic spirit. While examining some of the most essential problems and norms of the Canon, which in many cases have a moral, religious and legal character, I conclude that all these (problems and norms) take the roots of the Albanian Canon deep in antiquity, while, in the absence of a national state for all Albanian lands and the relevant state laws of the nation, the Canon emerges as a means of protection of provincial and inter-provincial ties and as an expression of national consciousness. The purpose of this paper is to approximate the truth of the antiquity of the Canon as well as its authorship, as it survived for centuries as an unwritten but applied document. Methodology: Research method and synthesis method.